Assessment of the Recent Hydromorphological Features of Nokoue Lake and Its Channels (South-East Benin) - Yonouwinhi, Tètchodiwèï Julie-Billard; d’ALMEIDA, Arsène F.; Abagale, Felix Kofi; AKOWANOU, Akuemaho Virgile Onésime (My University, 2024)
Based on 2022 and 2023 hydrometric data and satellite images (Sentinel 2022, SPOT 2010), this study aims to present the Nokoué Lake and its channels’ re-cent hydromorphological characteristics. Integrating flow, tributary mor- phology, and topography data determined specific power values along the axes studied. The values obtained range from 2.69 to 12.92 W/m2 for Ouémé River and 2.46 to 10.99 W/m2 for Sô River. The resulting water erosion on banks and bottoms is of linear, areolar, or gully and claw types. Lake bathy- metry varies from −0.5 to −2.6 m (low flow period) and −1 to −4 m; in the Ouémé, Sô, and Totchè rivers, it varies from −5 m to −7 m, reaching −10 m at the Cotonou channel entrance (flood period). Bathymetric profiles reveal va- ried “U”, “V” and “Intermediate” bottom morphologies, influenced by ero- sion/sedimentation processes and human activities. The flow facies identified are lentic in the northern tributaries and lotic in the Cotonou and Totchè canals. Spatial analysis identified nine (09) thematic classes. In 2022, the sur- face area of the water body has increased from 274 km2 at low water to 280 km2 at high water, whereas in 2010 (a recent year of exceptional flooding), the surface area was 270 km2 at low water and 277 km2 at high water. Significant changes in land use are observed between 2010 and 2022. The floodplain area decreased slightly, from 421 km2 in 2010 (year of exceptional flooding) to 419 km2 in 2022. The evolution of land use shows a progressive expansion of the urban environment to the detriment of the natural environment. In the me- dium to long term, this trend could threaten the hydromorphological balance and even the existence of this important lagoon ecosystem.
Keywords: Nokoué Lake; Ouémé River; Sô River; Cotonou Channel; Hydromorphology